Construção de uma plataforma configurável para aquisição de imagens com aplicações pupilométricas - John Kennedy Schettino de Souza (2012)
Accurate measurements of the pupils dynamics can be performed through pupillometry, a non-invasive test from which objective indexes of physiological nature can be extracted. Such indexes, working individually or in a combined form, allow the assessment of the nervous systems behavior and identify occasional abnormalities. One of the great problems of researches based on pupillometric information lies on the tools specification. Therefore, the challenge in this work was to develop a low cost, reconfigurable tool (hardware/software) that allows the study of pupil from various approaches, demonstrating its applicability throughdistinct experiments. As a result of this work, an image-acquisition platform was build, whose evaluation identified a temporal resolution of 1/120 Hz and a spatial resolution of 0.03 mm, placing our platform inside the range (120Hz / 0.01 to 0.1 mm) of the various commercial products and prototypes. Among the advantages of that platform are ease of synchronization, as well as of identification and recovery of capture failures. With that platform, two distinct configurations were set (hardware/software) and applied in pilot studies of the lightspupillary reflex on the burrowing owl (Athene cunicularia) and in the assessment of sleep deprivation in humans. The results showed that the owls pupillary constriction is 5 times faster than that of primates. As for the assessment of sleepiness, the study showed the possibility of identification of sleep-deprived subjects by using the combination of 3 indexes: reaction time, oscillation of the pupils diameter and long blinking time.